2022
DOI: 10.1111/hae.14526
|View full text |Cite
|
Sign up to set email alerts
|

Impact of first COVID‐19 lockdown on paediatric and adult haemophilia patients treated in a French Haemophilia Comprehensive Care Centre

Abstract: Introduction The coronavirus disease 2019 (COVID‐19) pandemic has created an unprecedented global health crisis. Aim To investigate the impact of the 1st COVID‐19 lockdown on haemophilia patients in terms of symptoms, management, medication adherence, mental health and lifestyle behaviours. Methods A prospective cross‐sectional phone survey using a two‐part questionnaire was conducted in haemophilia patients (adults and children) followed‐up in a French Haemophilia Comprehensive Care Centre between May 5, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The analysis of the main study variables during the COVID-19 pandemic, by lockdown period, although limited by variability in the number of evaluable patients in each period, contributes to a better understanding of the impact of the strict social and activity limitations adopted by the Italian government during the pandemic. Differently from other studies depicting a decrease in PA among adolescents and young adults during the first COVID-19 lockdown in the Netherlands [ 37 ], Norway [ 9 ], and France [ 38 ], our study did not reveal any impact on the PA recorded both in the first and second lockdown. It is important to consider that the observation period in our ad hoc analysis was longer, all data related to PA were monitored (not only sports), and the data collection solution was more accurate despite the e-survey.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The analysis of the main study variables during the COVID-19 pandemic, by lockdown period, although limited by variability in the number of evaluable patients in each period, contributes to a better understanding of the impact of the strict social and activity limitations adopted by the Italian government during the pandemic. Differently from other studies depicting a decrease in PA among adolescents and young adults during the first COVID-19 lockdown in the Netherlands [ 37 ], Norway [ 9 ], and France [ 38 ], our study did not reveal any impact on the PA recorded both in the first and second lockdown. It is important to consider that the observation period in our ad hoc analysis was longer, all data related to PA were monitored (not only sports), and the data collection solution was more accurate despite the e-survey.…”
Section: Discussioncontrasting
confidence: 99%
“…It is important to consider that the observation period in our ad hoc analysis was longer, all data related to PA were monitored (not only sports), and the data collection solution was more accurate despite the e-survey. On the other hand, our results confirm those from other studies revealing that patients’ well-being and lifestyle, treatment adherence, bleeding frequency, pain, and painkiller use were not affected by the pandemic [ 9 , 36 , 38 ].…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed a decrease in PA among PWH in March‐May 2020, which is natural, since this coincides with the first COVID‐19 lockdown in Norway, when strict social and activity restrictions were imposed, including closing of gyms and schools. Decreased PA of PWH during this period has also been reported from surveys in the Netherlands and France 42,43 …”
Section: Discussionsupporting
confidence: 69%
“…Studies have shown that the COVID-19 pandemic had a negative impact on lifestyle behaviors, routine care, and replacement therapies in patients with CBD [15][16][17][18]. However, there are only a limited number of clinical studies that have investigated the outcomes of COVID-19 in patients with bleeding disorders, and it is not known whether patients with bleeding disorders are more or less prone to the severe form of infection.…”
Section: Discussionmentioning
confidence: 99%